Kontribusi Agroforestri Terhadap Peningkatan Kesejahteraan Petani di Desa Umauta, Kecamatan Bola, Kabupaten Sikka - Inggrida Ermelinda Wenggo; Lusia Sulo Marimpan; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Agroforestry is a land cultivation system that combines agricultural and forestry crops on one land. Agroforestry systems are widely implemented in East Nusa Tenggara, one of which is Umauta Village, Bola District, Sikka Regency. The agroforestry system provides benefits both in ecological, social and economic terms, one of which is income for farmers. Farmer income is influenced by crop composition. This research aims to identify the type of composition that provides the highest income and its impact on farmer welfare. This research was carried out in April-May 2024 using qualitative and quantitative methods. The data collected is primary and secondary data. Sampling uses techniques purposive sampling. The research results obtained through interviews were that there were 12 plant compositions in Umauta Village, Bola District, Sikka Regency. The composition with the highest income is composition 1 with the composition of Clove Nutmeg plants as the main plant and Vanilla, Pepper Candlenut, Avocado, Cocoa, Jackfruit, Coconut, Gamal plants as filler plants. Agroforestry systems contribute to total income of 91.02%. The welfare level of farmers in the prosperous category is 10%, while the not so prosperous category is 90%.